Eksekusi Hukuman Cambuk Saat Pandemi: Standar Ganda Pemerintah Aceh Terhadap Kebijakan Larangan Kerumunan - Faradilla Fadlia; Ismar Ramadani; Siti Nur Zalikha; Maghfira Faraidiany (Department of Government Studies, Universitas Syiah Kuala, 2023)
This paper will discuss how the implementation of whipping execution continues in Aceh even during the COVID-19 pandemic. This shows how the Aceh government continues to implement Islamic law through the law of caning rather than maintaining health and safety by avoiding crowds, considering that this law has requirements to be carried out in public and displayed. In other words, the caning is still carried out in open spaces even though it is stated that they have complied with health protocols. The hypothesis of this paper is that the Government has a double standard against the crowd prohibition policy. The government issued a ban on the community to congregate, but in the implementation of this whip execution, the government actually attracted the people to assemble in public places through the implementation of the caning law in public spaces. The method used is qualitative with literature studies and interviews. This research will be conducted in Banda Aceh, Aceh.